Emotional intelligence, empathy and tolerance to the diversity in students of education of a peruvian public university - Frisancho León, Augusto (2020)
The objectives of the research were, firstly, to determine the levels of emotional intelligence, empathy and tolerance to diversity in a sample of 181 students in education; secondly, to establish the relationship between the three study variables and, finally, to determine if there are differences in these variables due to sex, study cycle and religious denominations. The instruments used were the Meta-Mood Scale 24 Trait, the Cognitive and Affective Empathy Test, and a diversity tolerance instrument. The results arrived at indicate that most students have a high level of tolerance for diversity and empathy, and an average level of emotional intelligence. The relationship between scores of emotional intelligence and empathy was confirmed, as well as the scores between empathy and tolerance of diversity, but not between emotional intelligence and tolerance of diversity. Likewise, it was found that there is a difference in tolerance to diversity and in empathy between males and females, in favor of the latter; that there is no difference according to the cycle of studies in any of the variables studied; and that students who profess the Catholic religion present a higher level of empathy than non-believers.